Geoprocessing Model for Automation of Land Use Balance Analysis - Trisnanti Widi Rineksi; Tatag Bagus Narendra (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Land use balance analysis (NPGT) is essential for obtaining information on land ownership, use, and utilization, suitability to spatial planning, and land availability. By providing accurate and detailed data, NPGT can assist the government and stakeholders in making informed decisions regarding land allocation and use. Method in the land use balance analysis requires several stages, thus requiring time to process data. By using automation, data processing can be accelerated compared to conventional processing which requires many stages. This study aims to create a geoprocessing tool in ArcGIS Pro to shorten the processing stages and be able to produce primary analysis in the form of changes in use, suitability, and directions for land availability. By applying the geoprocessing model for land use balance sheet analysis, better performance was obtained compared to conducting conventional analysis with an average time of 2.5 minutes. This automation tool has also been tested using the System Usability Scale method where the results obtained with an average score of 72, which is in the acceptable category.